Generating power-optimal standard cell library specification using neural network technique - Lim, Sze Huang; Lim, Yang Wei; Mashohor, Syamsiah; Kamsani, Noor Ain; Mohd Sidek, Roslina; Hashim, Shaiful Jahari; Rokhani, Fakhrul Zaman (IEEE, 2017)
In VLSI semi-custom design approach, power-optimal standard cell library selection for a given block design requires time-consuming iterative processes. This paper presents a framework to select a standard cell library that can result in near-optimal power while satisfying targeted frequency. The framework relies on neural network model to quickly predict the total power of a block design associated with a given standard cell library in order to speed up the synthesis process. The experimental result based on various synthesized benchmark circuits demonstrated the effectiveness of proposed framework for near-optimal standard cell library specification.